AgNPs-GO / SilMA composite hydrogel as well as preparation method and application thereof
Through the use of AgNPs-GO/SilMA composite hydrogel, the problem that existing antibacterial materials are difficult to meet the antibacterial and osteogenic effects at the same time is solved, and the efficient antibacterial and osteogenic effects in the repair of bone defect infection is achieved.
Patent Information
- Application Number
- CN202411543539.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing antibacterial materials are difficult to meet the requirements of both antibacterial and osteogenic effects, especially in the repair of irregular infectious bone defects.
AgNPs-GO/SilMA composite hydrogel is used, which consists of nanosilver particles-graphene oxide (AgNPs-GO) and methacrylylated silk fibroin (SilMA), and is used to make it light in ultraviolet light through a photoinitiator. The cross-linking and curing are lowered to form a composite hydrogel with antibacterial and osteogenic functions.
This composite hydrogel has excellent antibacterial effect in the repair of bone defect infection and has good osteogenic properties. It can promote the osteogenic differentiation of stem cells and is suitable for the repair of irregular infectious bone defects.
Smart Images

Figure CN119391007A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials, and in particular relates to an AgNPs-GO / SilMA composite hydrogel and a preparation method and application thereof. Background Art
[0002] In the field of materials, the preparation of antibacterial materials is mainly to kill bacteria by adding antibacterial ingredients. Antibacterial ingredients are a class of substances with antibacterial and bactericidal properties, and are the core of antibacterial materials. Antibacterial ingredients can be roughly divided into organic low molecular weight, organic high molecular weight, natural extract antibacterial agents and composite antibacterial ingredients.
[0003] In the repair of bone defect infection, the ideal antibacterial material not only needs to have a good antibacterial effect, but also needs to have a good osteogenesis effect to form a scaffold to support the material itself.
[0004] Existing antibacterial materials cannot meet the requirements of antibacterial and osteogenesis at the same time, or cannot be used in the repair of irregular infected bone defects. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to propose a composite hydrogel, which uses methacryloylated silk fibroin (SilMA) as a scaffold and combines nanosilver particles-graphene oxide (AgNPs-GO) to form a photosensitive injectable multifunctional composite AgNPs-GO / SilMA with a species-specific mechanism, which can be used as a highly effective antibacterial agent in the repair of bone defect infection.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0007] The invention discloses an AgNPs-GO / SilMA composite hydrogel, which comprises a photoinitiator, nano silver particles-graphene oxide and methacrylylated silk protein. The methacrylylated silk protein with the photoinitiator is dissolved in the nano silver particles-graphene oxide solution to obtain a hydrogel precursor liquid. When used, the hydrogel precursor liquid is cross-linked and cured into a hydrogel under ultraviolet light.
[0008] Silver nanoparticles (AgNPs) have good antibacterial properties and can effectively inhibit the growth of many bacteria;
[0009] Silver nanoparticles-graphene oxide (AgNPs-GO): The formation mechanism is that the functional groups (hydroxyl, epoxide, carbonyl and carboxyl) uniformly exist on the basal plane and edges of graphene oxide (GO), which can act as nucleation sites for AgNPs. + The electrostatic interaction between Ag and the negatively charged graphene oxide groups is + Provides multiple binding sites to form Ag+ -GO composites to prevent AgNPs from agglomerating. + and GO is gradually reduced to AgNPs on the surface of GO by the reducing agent. The AgNPs-GO composite is formed by chemical bond formation or simple electrostatic attraction between GO and AgNPs. The AgNPs-GO composite exhibits excellent antibacterial activity against several Gram-negative and Gram-positive bacteria, including Escherichia coli, Enterococcus faecalis, etc.
[0010] Methacryloylated silk fibroin (SilMA): Silk fibroin (SF) is derived from the degumming of silk and is a high molecular weight polypeptide composed of multiple amino acids. The SF molecule includes a hydrophobic peptide chain (H chain) and a hydrophilic peptide chain (L chain). The various properties of silk fibroin materials can be effectively controlled by regulating the secondary structure of silk fibroin, including the preparation of high-strength and high-oriented materials. SF has good biocompatibility, biodegradability, high tensile strength and other characteristics. Methacryloylated silk fibroin (SilMA) is modified by methacrylating SF with glycidyl methacrylate, and double bonds are introduced into the SF molecule. Due to the special spatial structure of the SF molecule, it is very easy to form crystals and is difficult to dissolve in water before modification. After the introduction of additional chemical groups, it can be quickly dissolved in the nanosilver particle-graphene oxide solution, which allows SilMA to be photocured into a composite hydrogel.
[0011] One of the applications of the AgNPs-GO / SilMA hydrogel of the present invention is that it can be used as an antibacterial agent in the treatment of refractory periapical periodontitis in oral medicine. Refractory periapical periodontitis is an oral disease characterized by a dominant flora dominated by Enterococcus faecalis. The present invention is a material with broad-spectrum antibacterial ability. The present invention has been proven to have good antibacterial effects through antibacterial experiments on Escherichia coli and Enterococcus faecalis.
[0012] This composite material combines the antibacterial properties of AgNPs, the mechanical strength of GO, and the stable degradation and osteogenic properties of SilMA, as well as good biosafety and photoresponsive properties. This material has application prospects in the repair of irregular infected bone defects in combination with stem cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the SEM scanning electron microscope image of AgNPs-GO / SilMA composite hydrogel;
[0014] Figure 2 EDS spectrometer measurement of AgNPs-GO / SilMA composite hydrogel;
[0015] Figure 3is the Fourier transform infrared analysis (FT-IR) of AgNPs-GO / SilMA composite hydrogel; a is the original image overlap analysis diagram of each concentration group curve obtained after Fourier transform infrared analysis; b is the calibration diagram of the functional groups in AgNPs-GO / SilMA composite hydrogel;
[0016] Figure 4 is the relationship between the viscoelastic properties of AgNPs-GO / SilMA composite hydrogel and the frequency;
[0017] Figure 5 Schematic diagram of the mechanical properties of AgNPs-GO / SilMA composite hydrogel; from left to right are the compression curves of hydrogels with different concentrations and the corresponding compression modulus diagrams;
[0018] Figure 6 This is a diagram of the injection performance of the AgNPs-GO / SilMA composite hydrogel; from left to right, it is a diagram of the AgNPs-GO / SilMA composite hydrogel stock solution, a diagram of the tip of the needle in the syringe forming a drop shape, and a diagram of the writing effect of the syringe in the culture dish;
[0019] Figure 7 This is the degradation performance test diagram of AgNPs-GO / SilMA composite hydrogel;
[0020] Figure 8 The pore swelling diagram of AgNPs-GO / SilMA composite hydrogel; the upper diagram corresponds to the porosity, and the lower diagram corresponds to the swelling rate;
[0021] Fig. 9 The antibacterial activity of AgNPs-GO / SilMA composite hydrogel against Escherichia coli and Enterococcus faecalis was determined;
[0022] Fig.10 The cell biocompatibility of AgNPs-GO / SilMA hydrogel to hBMSCs; corresponding to CCK-8 test results (left) and cell live-dead staining (right);
[0023] Fig.11 The effect of AgNPs-GO / SilMA hydrogel on the osteogenic differentiation of hBMSCs; corresponding to WB experiment (left), WB quantitative analysis results (upper right), and qPCR quantitative analysis results (lower right);
[0024] Fig.12 The ALP activity and mineralized nodules of hBMSCs were determined after co-culture of hBMSCs with AgNPs-GO / SilMA composite hydrogel for 21 days. DETAILED DESCRIPTION
[0025] In order to allow those skilled in the art to understand the present invention more clearly and intuitively, the present invention will be further described below in conjunction with the accompanying drawings.
[0026] Preparation of SilMA:
[0027] Take 20g of silkworm cocoons and add 100ml of 0.05M Na2CO3, and heat for 30min to remove sericin. Then wash repeatedly with deionized water several times and dry at 70℃ for 48h. Then dissolve in 100ml of 9.3M lithium bromide solution. After that, gradually add 6ml of GMA (424mm, Sigma-aldrich), stir at 60℃, 300rpm for 4h, and dialyze continuously in a 12-14KDa cutoff bag for 7 days, changing deionized water every day. Finally, freeze-dry the SilMA solution and store it at -20℃ until use.
[0028] Preparation of AgNPs-GO:
[0029] First, graphene oxide was dispersed in deionized water by ultrasonic oscillation for 4 h until it was completely dispersed to obtain a 1 mg / mL graphene oxide solution.
[0030] Then, 20 mL of 1 mg / mL graphene oxide solution was added to 40 mL of 10 mg / mL tannic acid solution, and the mixed solution was ultrasonicated for 30 min.
[0031] Next, 1 mol / mL NaOH solution was added dropwise to the mixed solution until the pH was neutral.
[0032] Finally, 2.353 mL of 50 mmol / mL AgNO3 solution (mass ratio of GO to Ag is 1:1) was added, at which point the color of the solution changed from brown-black to brown-yellow, and the reaction was stopped after stirring for 30 min.
[0033] In order to obtain AgNPs-GO solutions of different concentrations, the following volumes need to be taken from the initially prepared solution:
[0034] 20μg / mL: Take 0.00098mL (about 0.98μL) and add deionized water to make up to 10mL.
[0035] 40μg / mL: Take 0.00197mL (about 1.97μL) and add deionized water to make up to 10mL.
[0036] 60μg / mL: Take 0.00295mL (about 2.95μL) and add deionized water to make up to 10mL.
[0037] Preparation of AgNPs-GO / SilMA hydrogel:
[0038] Prepare four centrifuge tubes, and weigh 150 mg of SilMA solid and 10 mg of 2,4,6-trimethylbenzoyl (LAP photoinitiator) into each of the four centrifuge tubes.
[0039] 1 ml of AgNPs-GO solution with concentrations of 0ug / ml, 20ug / ml, 40ug / ml, and 60ug / ml was added to four centrifuge tubes respectively to dissolve the solid to obtain precursor solutions, which were named 0-SillMA group, 20-SillMA group, 40-SillMA group, and 60-SillMA group. The mass volume fraction of SillMA was 150 mg / 1 mL × 100% = 15 wt%.
[0040] The reaction was started in a magnetic stirrer at 400 rpm for 2 hours under light protection. After the reaction, the composite hydrogel solution was added to the mold and then irradiated with 405 nm ultraviolet light for 15-30 seconds to completely crosslink it into a gel state.
[0041] The four prepared AgNPs-GO / SilMA composite hydrogels were freeze-dried and a small amount was scanned by SEM electron microscope. The images are shown in Figure 1 As shown, the typical honeycomb voids of GelMA hydrogel are displayed, and the composition of AgNPs loaded in SilMA does not affect the obvious change of its voids.
[0042] Then we used the prepared 20-SillMA group, 40-SillMA group, and 60-SillMA group of three AgNPs-GO / SilMA composite hydrogels containing silver ions to perform EDS spectrum analysis. The results of elemental analysis of the experimental group scaffolds are shown in Figure 2 The results show that the peak of Ag element is displayed at the binding energy of 3.0keV, indicating that after confirming that AgNPs-GO / SilMA composite hydrogel has successfully introduced Ag element through EDS energy spectrum analysis, we need to further verify the existence of other components.
[0043] We performed FT-IR (Fourier transform infrared analysis) on the prepared AgNPs-GO / SilMA composite hydrogels of various concentrations. Figure 3 In Figure a, the components are proved by the physicochemical analysis of characteristic functional groups. It is the overlap analysis of the original images of the curves of each concentration group obtained after Fourier infrared analysis. Through the overlap of the curves, we can see that the curves of each component have a good overlap, which proves that a small amount of loading of AgNPs-GO will not affect the change of the overall performance of the scaffold. Figure 3 Figure b shows the calibration of functional groups. The stretching vibration peak of gelatinamide (amino group) is located at 3400-3300 cm -1 Between; at 1640cm-1 This peak corresponds to the α-helical structure in silk protein; 1556cm -1 It is mainly caused by the stretching vibration of the aromatic hydrocarbon C=C skeleton of graphene oxide; the three characteristic functional group peaks just correspond to SilMA and GO in the components, proving that the presence of SilMA and GO can be detected in the AgNPs-GO / SilMA composite hydrogel.
[0044] After confirming the individual components one by one, the next step is to measure the gel properties of the SilMA hydrogel to show its own gel properties. Figure 4 ), the temperature and strain are constant, and the relationship between viscoelastic properties and frequency is investigated. The experimental results clearly show that G' of all hydrogel groups exceeds G" in the frequency range of 0.1-100rad / s. When a given material shows G'>G", this indicates that the elasticity level is greater than the viscosity level, which is consistent with hydrogel-like behavior rather than solution-like behavior, proving that the AgNPs-GO / SilMA synthesized in this experiment does have hydrogel properties; in addition, it was found that increasing the concentration of AgNPs-GO can optimize the rheological properties of SilMA hydrogel, but when the concentration of AgNPs-GO increases to 60μg / mL, the rheological properties decrease instead; the rheological properties of 40μg / mL concentration are better; considering that a higher concentration of AgNPs-GO will excessively increase the mechanical strength of the hydrogel, resulting in the hydrogel being too hard, the rheological properties will decrease instead.
[0045] Bone tissue engineering carriers are often required to have good mechanical properties, which can protect the loaded or coated active ingredients from mechanical damage and reduced efficacy before they degrade. Therefore, this experiment used a tensile fracture stress test to test whether the introduced AgNPs-GO would affect the mechanical properties of the SilMA hydrogel system. The experimental results showed that ( Figure 5 ) The material of the pure SilMA group curve broke at 50% strain, with a force of about 40 kPa; the 20-SilMA red curve group broke at 70% force; the 40-SilMA blue curve group broke at 90% force; the 60-SilMA purple curve group broke at 60% force; combined with the statistics of compression modulus, it can be concluded that increasing the concentration of AgNPs-GO can improve the mechanical properties of SilMA, but when the concentration of AgNPs-GO is too high, the material will become harder, the brittleness will increase, and the stress fracture will occur earlier. Therefore, choosing a moderate concentration of AgNPs-GO can effectively enhance the mechanical properties of SilMA hydrogel. Adding 20-40μg to the SilMA hydrogel system
[0046] / mL concentration of AgNPs-GO has a higher improvement on mechanical properties.
[0047] Injectable hydrogels are considered smart materials and are widely studied for their use as scaffolds. They resemble the extracellular matrix of natural tissues and can be uniformly mixed with therapeutic agents. They can be implanted in living bodies with minimal invasiveness and are suitable for irregularly shaped sites. Bone tissue defects are often irregular, and uniform hydrogels obviously do not meet the actual treatment needs of clinical treatment. SilMA hydrogel precursor has good injectability. This experiment ( Figure 6 ) Through methylene blue staining, it can be found that it has a certain injection ability after injection with a syringe. Finally, the English abbreviation "SMU" of Southern Medical University is written in the culture dish with it to prove its good injection ability. These unique characteristics make SilMA composite hydrogel a material with strong practicality in the field of bone tissue engineering. It should be noted that the freshly configured AgNPs-GO / SilMA will have color (yellowish), and AgNPs-GO will decompose and become colorless over time. Therefore, Figure 6 The AgNPs-GO / SilMA composite hydrogel in the middle left picture is a colorless liquid. Figure 7 The degradation rate of AgNPs-GO / SilMA was lower than that of GelMA, although they both gradually degraded over time in collagenase solution. In general, silk fibroin can effectively reduce the degradation performance of hydrogel microspheres, which is attributed to its own controllable degradation performance. The overall results show that AgNPs-GO / SilMA is more stable than GelMA, which is desirable for bone defect treatment.
[0048] At present, most bone tissue engineering scaffolds are porous structures. The purpose of the pores is to provide space for cells to adhere and proliferate, thereby promoting the proliferation of seed cells. In addition, the porous structure is conducive to increasing the contact area between the scaffold material and the human body's liquid environment, allowing the inside of the scaffold to exchange substances with the microenvironment, thereby improving the potential of the scaffold in drug loading and release. The experiment used the pycnometer method to measure the porosity of scaffolds containing different proportions of AgNPs-GO. The results are shown in Figure 2. Figure 7 As shown. The average porosity of the scaffold with AgNPs-GO added to SilMA was slightly lower than that of the 0 mg / mL group (0-SilMA group), which may be due to the fact that AgNPs-GO occupied a certain space inside the scaffold. However, there was no statistical difference in the porosity between the groups (P>0.05), so loading a small amount of AgNPs-GO did not cause a significant change in the porosity of the scaffold, and did not affect the material exchange and cell adhesion properties of the scaffold. Figure 7The results of the water absorption and swelling rate measurement of the AgNPs-GO scaffolds showed that the swelling rate of the scaffolds with the addition of AgNPs-GO was slightly lower than that of the 0mg / mL group (0-SilMA group). However, there was no statistical difference in the swelling rate between the experimental groups (P>0.05), indicating that the loading of a small amount of AgNPs-GO did not cause a significant change in the swelling rate of the scaffold and did not change its stability.
[0049] To explore the antibacterial properties of the scaffold, the antibacterial ability of the composite scaffold containing AgNPs-GO was analyzed by colony plate counting and inhibition zone transparent ring test. The control group and each test group specimens were co-cultured with Escherichia coli and Enterococcus faecalis for 24 hours and the colony counts of adherent bacteria were performed. Figure 8 ) showed that, with the 0-SilMA group as the blank control, it can be seen that the 0-SilMA group without the addition of AgNPs-GO had more bacteria adhering to the surface of the specimens, while the number of bacteria adhering to the surface of the experimental groups (20-SilMA group, 40-SilMA group, 60-SilMA group) with the addition of AgNPs-GO was significantly less than that of the control group (P < 0.05). And with the increase in the proportion of AgNPs-GO, the number of bacteria adhering to the specimens in the experimental groups gradually decreased, and the differences between the experimental groups were statistically significant (P < 0.05). Figure 8 It can be seen that the antibacterial rate of the 20μg / mL group is lower. The antibacterial rate of the 40 / 60μg / mL group is higher. From the experimental results, the new SilMA composite hydrogel containing AgNPs-GO synthesized in this experiment has a good antibacterial effect on Escherichia coli and Enterococcus faecalis.
[0050] After verifying the material characterization of the scaffold, the in vitro cell functional verification was carried out to screen out the appropriate concentration. First, AgNPs-GO / SilMA containing different AgNPs-GO concentrations (0μg / mL, 20μg / mL, 40μg / mL, 60μg / mL) was co-cultured with human bone marrow mesenchymal stem cells (hBMSCs) for 1d, 3d, and 5d, respectively. The results are as follows: Fig. 9 As shown, it was found that at 1d, 3d, and 5d, the 60μg / mL concentration group had strong cytotoxic side effects, while there was no significant difference between the AgNPs-GO / SilMA and CON group (pure water group) at 0μg / mL, 20μg / mL, and 40μg / mL AgNPs-GO concentrations. In order to further verify the results of CCK-8, we selected the third day of co-culture for live-dead staining experiments. The results showed that there was no significant difference between the AgNPs-GO / SilMA and CON group at 0μg / mL, 20μg / mL, and 40μg / mL AgNPs-GO concentrations, and the 60μg / mL group had strong cytotoxic side effects, which was consistent with the results of CCK-8.
[0051] After seven days of co-culture with hBMSCs, WB results showed that AgNPs-GO / SilMA in the 40 μg / mL AgNPs-GO concentration group could promote the increase of ALP, RUNX2, and BMP2 protein levels in hBMSCs, and was concentration-dependent within the set concentration gradient range. With the increase of concentration, the osteogenic effect increased ( Fig.10 ). After seven days of co-culture with hBMSCs, qPCR results showed that AgNPs-GO / SilMA in the 40 μg / mL group could promote the increase of ALP, RUNX2, and BMP2 RNA levels in hBMSCs, and was concentration-dependent within the set concentration gradient range. With the increase of concentration, the osteogenic effect increased.
[0052] like Fig.11 As shown, after seven days of co-culture with hBMSCs, the results of ALP activity assay proved that AgNPs-GO / SilMA in the 40 μg / mL group could promote the alkaline phosphatase activity of hBMSCs; Fig.12 As shown, the results of mineralized nodule formation after 21 days of co-culture with hBMSCs proved that AgNPs-GO / SilMA in the 40 μg / mL group could promote the formation of mineralized nodules of hBMSCs, and was concentration-dependent within the set concentration gradient range. With the increase of concentration, the osteogenic effect increased.
[0053] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.
Claims
1. An AgNPs-GO / SilMA composite hydrogel, characterized in that: The method comprises a photoinitiator, nano silver particles-graphene oxide and methacrylylated silk protein, wherein the methacrylylated silk protein with the photoinitiator is dissolved in the nano silver particles-graphene oxide solution to obtain a hydrogel precursor liquid; When in use, the hydrogel precursor liquid is cross-linked and cured into a hydrogel under ultraviolet light.
2. The AgNPs-GO / SilMA composite hydrogel according to claim 1, characterized in that: The concentration of the AgNPs-GO solution is 20-40 μg / mL.
3. The AgNPs-GO / SilMA composite hydrogel according to claim 1, characterized in that: The photoinitiator is 2,4,6-trimethylbenzoyl.
4. The AgNPs-GO / SilMA composite hydrogel according to claim 2, characterized in that: The mass volume concentration of the methacrylylated silk fibroin solution is 15 wt %.
5. The AgNPs-GO / SilMA composite hydrogel according to claim 1, characterized in that: The wavelength of ultraviolet light is 405nm.
6. The method for preparing the AgNPs-GO / SilMA composite hydrogel according to any one of claims 1 to 5, characterized in that: The steps include: (1) Weigh SilMA solid and photoinitiator into a container; (2) Adding AgNPs-GO solution into a container, reacting in a magnetic stirrer under light protection to obtain a hydrogel precursor solution, and then cross-linking into a gel state by ultraviolet irradiation.
7. The preparation method according to claim 6, characterized in that: The concentration of the AgNPs-GO is 20-40 μg / mL.
8. The preparation method according to claim 6, characterized in that: The photoinitiator is 2,4,6-trimethylbenzoyl.
9. The preparation method according to claim 6, characterized in that: The wavelength of ultraviolet light is 405nm.
10. Use of the AgNPs-GO / SilMA composite hydrogel according to any one of claims 1 to 5 as an antibacterial agent in the repair of refractory periapical periodontitis and irregular infected bone defects.
Citation Information
Patent Citations
Sericin / oxidized graphene composite hydrogel as well as preparation method and application thereof
CN109054047A
Preparation method of novel methacrylic anhydride modified fibroin
CN114773549A
Preparation method of silk fibroin hydrogel
CN116854872A